Digital Transformation in Public Service: Mapping Research Trends, Emerging Themes, and Future Research Directions Through Bibliometric Analysis - Ni Wayan Desi Budha Jayanti; Muhammad Khafid Ainul Yaqin; Gusti Naufal Rizky Perdana; Yaen Miftakhul Laily (Manunggal Halim Jaya, 2026)
Digital transformation has become a strategic priority in public service reform to improve efficiency, transparency, and inclusivity. Despite the rapid growth of research in this field, existing studies remain fragmented, with limited attention to governance challenges, inclusivity, and the broader implications of digital transformation for public sector governance. This study aims to identify research trends, intellectual structures, knowledge gaps, and future research directions in digital transformation within public services. A bibliometric analysis was conducted on 574 Scopus-indexed publications published between 2012 and 2025 using the Bibliometrix package in RStudio. The findings reveal a substantial increase in publications after 2020, reaching a peak in 2024, largely driven by accelerated digital adoption during the COVID-19 pandemic. Keyword co-occurrence analysis identifies digital transformation, public services, e-government, and public administration as dominant research themes, while artificial intelligence, smart cities, blockchain, and sustainability emerge as rapidly growing topics. Geographical analysis indicates significant contributions from Russia, Germany, and Indonesia, reflecting the global relevance of digital transformation across diverse governance contexts. This study contributes by systematically mapping the intellectual landscape of the field, identifying underexplored governance and inclusivity issues, and proposing future research directions that integrate advanced digital technologies with sustainability and citizen-centered public service governance.